Dynamics Simulation Analysis of the Slewing Gear Meshing of Anti-radiation Hydraulic Excavator - Liu Jun; Zou Shuliang; Tang Dewen; Yuan Lianxiong (Jixie chuandong)
Taking the slewing gear of anti- radiation hydraulic excavator as study object,the 3D model of slewing gear is established by using Pro / E,the correct meshing parameters of slewing gear meshing transmission are determined,and the slewing gear mesh dynamics simulation is carried on in ADAMS. The simulation results of rotating speed of gear ring,meshing force and the frequency of the meshing force are much the same as the theoretical calculation value,the accuracy and reliability of the model are verified. Finally,the influences of different rotation speed and torque on meshing force are analyzed. The simulation results can provide the basis of the calculation for strength check and optimization design of slewing gear.